Development of methods and means to improve environmental, radiation and industrial safety of NPPs with WWER-1200 - K. N. Proskuryakov; M. S. Khvostova (Глобальная ядерная безопасность)
The introduction provides an overview of scientific research on the sources of generation, characteristics and classification of infrasound. It is noted that infrasound has a number of features related to the low oscillation frequency of the elastic medium and the diffraction property. Infrasound has harmful effects on hearing, breathing, vision, gastrointestinal tract, nervous and cardiovascular systems, brain and vestibular apparatus, leading to decreased performance, general malaise and premature aging of the human body. The methodology of theoretical substantiation of methods for detecting previously unknown sources of infrasound, improving the environmental, radiation and industrial safety of nuclear power plants with WWER-1200 is based on the use of digital acoustic models of primary circuit equipment responsible for operational safety developed under the guidance of K.N. Proskuryakov. The methodology of practical confirmation of the results of computational and theoretical forecasting of acoustic parameters of previously unknown infrasound sources is presented in the form of two stages: a) development of a methodology for verifying forecasting results and selection of power units No. 1, 2 of Novovoronezh NPP-2 in the form of objects; b) investigation of the conditions for the occurrence of vibro-infrasound resonances in the first circuit. The developed method for investigating infrasound sources has been verified at the WWER-1200 reactor plant. When discussing the results of the conducted research, previously unknown sources of infrasound were identified. Innovative methods of analysis and damping of infrasound sources have been developed and a patent for invention No. 2803181 «A method for preventing resonant interaction of vibrations of water-water power reactor equipment with acoustically standing waves and a device for its implementation» has been obtained. The errors of the chief designer of reactor installations with WWER in the regulations for the launch of new power units are noted; their negative consequences for the health of personnel and the condition of equipment responsible for environmental, radiation and industrial safety of nuclear power plants with WWER are indicated